Generation Z and Millennial Perceptions of the Effectiveness of Digital Public Services: A Case Study of the Population and Civil Registration Service of Buleleng Regency - Ni Putu Liana Stanel Andini; Ida Bagus Teddy Priantara (Bulletin of Community Engagement, 2026)
The digital transformation has fundamentally reshaped public service delivery in Indonesia, particularly in Buleleng Regency, where the Department of Population and Civil Registration Service conducts a digital public service by implementing the application of “AKU ONLINE NG”. The current study aimed at investigating the generation Z and millennials perceptions towards the effectiveness of digital public services at the Department of Population and Civil Registration Service in Buleleng Regency. The mix-method approach was employed in the form of an explanatory sequential design. There were 40 users selected by using purposive sampling in which they were 12 millennials and 28 gen Z. The qualitative data were collected through interview with the interview guide as research instrument. Meanwhile, the quantitative data were obtained through survey by distributing close-ended questionnaires. The qualitative data were analysed by using Qualitative Data Analysis, meanwhile the quantitative data were analysed by using descriptive statistic and inferential statistic (independent sample t-test). The findings showed that the application was perceived as highly effective by gen Z and millennials indicated by the mean score that was greater than 4.4. It was also found out that there was no significant difference between the preference of gen Z and millennials in using the digital public services. These implicate the sustainability of digital public service as a digital transformation in public sector.